Место и роль политической коммуникации в трансформации украинского общества - Барматова, С. (Социология: теория, методы, маркетинг, 2004)
The author analyses transformations which: 1) occur in the system of political communications; 2) are broadcast to a society through political discourse and determined
as parameters of political communication system. Being one of the most mobile spheres
reflecting changes occurring in a society, political communications are good for studies
on social transformations. They include subjective and objective aspects of social
interaction between society members; changes in communicative and rhetorical tradition always mean changes in political strategies: attributes and signals of political
changes are usually well seen in speech structures.